The Impact of Receiving Government Funds on Indications of Financial Data Falsification - Hestie Fagie (Journal of Contemporary Information Technology, Management, and Accounting, 2021)
Falsifying financial data is a terrifying finance scourge that "front burners" to discuss. Many people still think that financial data fraud only occurs in profit-oriented organizations. However, it can also happen to non-profit organizations such as universities. Based on ICW data for 2006-2016, there were 37 corruption cases with 14 procurement cases. Other research also explains the procurement of goods and services that are not based on Purchase Order specifications and costs given to the purchasing department. The study focused on whether there were indications of financial fraud and the effect of receiving government funds on indications of university financial fraud. The research method used a questionnaire and analysis of the financial statements of selected universities. Data analysis used the benefit index ratio and regression analysis. The results showed 21.93% of the total answers from 43 respondents stated that they found indications of falsification of financial data in tertiary institutions and from 8 colleges 1 was declared a manipulator, 3 were declared a gray organization. Meanwhile, he explained that the receipt of government funds did not affect indications of falsifying higher education financial data.